1978
DOI: 10.1002/art.1780210910
|View full text |Cite
|
Sign up to set email alerts
|

Type C RNA virus expression in systemic lupus erythematosus. New Zealand mouse model and human disease

Abstract: An antigen recognized by antisera produced against p30 (core) proteins of the four chief groups of mammalian type C viruses (murine, feline, RD-114 related to endogenous primate, and infectious primate group) is located in an immune-complex pattern in some renal glomeruli of human SLE patients with lupus proliferative glomerulonephritis but is not detected in normal or pathological control human kidneys. This antigen crossreacts with p30 interspecies determinants shared by the four chief virus groups and cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
1981
1981

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Exogenous agents reported previously in association with SLE have included tubercle bacilli, streptococci, viruses, mycoplasmas, Haemobartonellae, tubular myxovirus structures, and type C viruses (1,13). However, the etiology of lupus remains unproved.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous agents reported previously in association with SLE have included tubercle bacilli, streptococci, viruses, mycoplasmas, Haemobartonellae, tubular myxovirus structures, and type C viruses (1,13). However, the etiology of lupus remains unproved.…”
Section: Discussionmentioning
confidence: 99%
“…The starting materials were human renal tissues obtained at postmortem examination of three patients with SLE described elsewhere (1,2). Briefly summarized, the duration of the disease in patients 1 and 2 was %/2 and 2 years, respectively; the SLE was associated with diffuse proliferative glomerulonephritis and showed typical glomerular deposits of host Ig and, less extensively, of type C viral p30-like antigen; the duration of the disease in patient 3 was 15 years; the SLE was not associated' with proliferative-type glomerulonephritis and showed glomerular deposits of host Ig but no detectable p30-like antigen.…”
Section: Methodsmentioning
confidence: 99%
“…Human systemic lupus erythematosus (SLE) is a multisystemic autoimmune syndrome of unknown etiology and multifactorial pathogenesis. Postmortem study of a subset of systemic lupus associated with proliferative glomerulonephritis has shown that an antigen related to the interspecies determinants of mammalian type C RNA viral core (p30) proteins is located in the renal glomerular lesions with human immunoglobulins (Igs) in an immune-complex pattern of deposition (1,2). We attempt to extend this finding by examining the immune deposits for the presence of a type C virus antibody.…”
mentioning
confidence: 99%